2016
DOI: 10.5771/0344-9777-2016-1-2-188
|View full text |Cite
|
Sign up to set email alerts
|

Pecularities of performance measurement in state-owned enterprises – The case of Lithuania

Abstract: Pecularities of performance measurement in state-owned enterprises -The case of Lithuania performance measurement; public economics; public organisations; public sector performance measurement; state-owned enterprise State-owned enterprises (SOEs) play a significant role in many economies. Consequently, this paper describes the key elements of SOE performance assessment and how they should be developed in order to improve the services and the quality of the products provided by SOEs. The analysis revealed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Additionally, SOEs in many nations use a sizable portion of the national resources of their owning nations, either increasing or depleting these resources. As a result, their effectiveness and efficiency play a significant role in determining the economic performance and competitiveness of the states they belong to (Kloviene andGimzauskiene 2016, Grossi et al 2015). Owning states, observers, and society as a whole cannot ignore these state enterprises in light of their importance, which has already been established.…”
Section: Athens Journal Of Business and Economicsmentioning
confidence: 99%
“…Additionally, SOEs in many nations use a sizable portion of the national resources of their owning nations, either increasing or depleting these resources. As a result, their effectiveness and efficiency play a significant role in determining the economic performance and competitiveness of the states they belong to (Kloviene andGimzauskiene 2016, Grossi et al 2015). Owning states, observers, and society as a whole cannot ignore these state enterprises in light of their importance, which has already been established.…”
Section: Athens Journal Of Business and Economicsmentioning
confidence: 99%
“…Xu and Birch (1999) concluded that this was the case for SOEs in the energy and electricity sectors in Argentina, while firms in service-oriented sectors focused on employment maximization. Kloviene and Gimzauskiene (2016) highlighted that using typical profitability and financial indicators as performance indicators for SOEs was not appropriate as these firms exhibit special features. Instead, they advise that accountability and performance regulators be evaluated using qualitative methods.…”
Section: Assessment Of the Performance Of State-owned Enterprisesmentioning
confidence: 99%
“…Additionally, SOEs in many states also utilise major national resources, with the possibility of either depleting or increasing these resources. Therefore, the effectiveness and efficiency of SOEs greatly influence the socioeconomic competitiveness and performance of shareholding states (Kloviene & Gimzauskiene, 2016;Grossi et al, 2015). Thus, government, observers as well as society cannot afford to neglect these state enterprises given their documented importance.…”
Section: Introductionmentioning
confidence: 99%